The Representation of the Indonesian Government in Media: A Critical Discourse Analysis of the Rempang Island Conflict - Fatinova, Dede; Gunawan, Wawan; Saifullah, Aceng Ruhendi; Risnawati, Eris; Emha, Ratna Juwitassari; Mubarok, Yasir (Universitas Pendidikan Mandalika, 2024)
The Indonesian government has come under intense scrutiny for its actions in the agrarian conflict in Rempang Island, Batam City, Riau Islands Province. The conflict was triggered by the government's forced relocation of the Rempang Island community in the context of the Rempang Eco City development funded by a foreign investor, Xinyi Group. The incident captured the attention of the public and the media due to the large scale of the case. This research aims to see how the Indonesian government is represented in the Indonesian news media regarding the discourse of the Rempang Island case. This research uses the theory of Critical Discourse Analysis initiated by Fairclough (1995) and Transitivity by Halliday (2014). The method used in this research is content analysis method to elaborate the image constructed by the media against the Indonesian government. The data in the study amounted to six data taken from Tempo.co media, and Batamnow.com which were analyzed through three stages, namely textual, discourse practices, and socio-cultural practices. The results showed that the Indonesian government was represented negatively by labeling it as the party that violated human rights and the perpetrator of crimes against humanity.